Análisis comparativo de las características cineantropométricas y de la condición física en jugadores de balonmano en edad juvenil - Jimenez Garcia. A. (2016)
Anthropometry parameters and physical condition are two key factors for de sporting success. Thus, the first objective of this study was to establish the morphological characteristics and different factors associated to the physical condition of the Ademar Leon Handball Club young players (n = 14). In order to reach this objective, the players were subjected to kinanthropometric valuation (such a height, weight, body mass index, skinfold thickness, diameters and body circumferences, somatotypes and percentage of body fat) and physical valuation condition, to measurethe explosive power of both upper and lower limbs, as well as other parameters as agility, speed and pitch speed. Subsequently, the second objective was to compare the results with other teams in the same category both Spain and abroad. By descriptive analysis of the results, we found that endomorphic component (5.61 ± 0.82) prevails in our population, comparing with other analyzed teams which dominate the mesomorphic component. Although kinanthropometric our team is lower, the results of physical tests state similarities and even improvements regarding the rest of the analyzed teams. Therefore, we conclude that the mesomorphic component associated to sporting success in our population, it is not as important as it is in other countries.